A recombinase-mediated system for elimination of antibiotic resistance gene markers from genetically engineered Bacillus thuringiensis strains. - Sanchis, V (1997)
A TnpI-mediated site-specific recombination system to construct genetically modified Bacillus thuringiensis strains was developed. Recombinant B. thuringiensis strains from which antibiotic resistance genes can be selectively eliminated were obtained in vivo with a new vector based on the specific resolution site of transposon Tn4430. For example, a cryIC gene, whose product is active against Spodoptera littoralis, was introduced into B. thuringiensis Kto harboring a cryIA(c) gene active against Ostrinia nubilalis. The resulting strain had a broader activity spectrum than that of the parental strain. It contained only B. thuringiensis DNA and was free of antibiotic resistance genes. This should facilitate regulatory approval for its development as a commercial biopesticide.